Health-related quality of life in outpatients with COPD in daily practice: the VICE Spanish study - Antonio Martín; José M Rodríguez-González Moro; José L Izquierdo; Elena Gobartt; Pilar de Lucas; The VICE Study Group (International Journal of COPD, 2008)
Antonio Martín1, José M Rodríguez-González Moro2, José L Izquierdo3, Elena Gobartt4, Pilar de Lucas2, The VICE Study Group1Medical Department, Pfizer, Madrid, Spain; 2Service of Pneumology, HGU Gregorio Marañón, Madrid, Spain; 3Service of Pneumology, Hospital General Universitario de Guadalajara, Guadalajara, Spain; 4Respiratory Area, Medical Department, Boehringer Ingelheim España, Madrid, SpainBackground: The objective of this study was to measure health-related quality of life (HRQL) in outpatients with chronic obstructive pulmonary disease (COPD) and to assess differences in HRQL according to age, gender, and severity of COPD.Methods: A total of 9405 patients (79% men, mean age 68 years) participated in a cross-sectional study. HRQL was measured with the Short Form 12 Health Survey Questionnaire (SF-12). Severity of COPD was graded into three levels according to forced expiratory volume in one second value.Results: COPD severity was mild in 33.8% of cases, moderate in 49.3% and severe in 16.8%. The mean physical component summary (PCS-12) and mental component summary (MCS-12) scores were 36.8 ± 10.4 and 47.2 ± 11.2, respectively. General health and physical functioning domains were those with the lowest scores. The mean MCS-12 scores were significantly higher in men (47.9 ± 10.9) than in women (44.1 ± 11.8) (P < 0.001). Patients older than 60 years rated HRQL worse than patients aged 40–59 years. There were statistically significant differences according to severity of disease in the mean scores of all domains of the PCS-12 and MCS-12 scales.Conclusions: The present findings show the influence of female gender, older age and moderate-to-severe of airflow limitation on HRQL in outpatients with COPD attended in daily practice.Keywords: health status, health surveys, multicenter study, pulmonary disease, chronic obstructive/epidemiology, quality of life, questionnaires